Future time perspective and group performance among students: Role of student engagement and group cohesion. (13th March 2020) - Gupta, Manish; Bakker, Arnold B.
Abstract : Purpose: The objective of this study is to understand the mediating role of student engagement between future time perspective and group task performance. In addition, the study examines the interaction effect of group cohesion task with student engagement on group performance. Design/methodology/approach: Data were collected from 170 (a total of 34 groups of five members each) business management students for three consecutive months. To analyze the data, multi-level modeling was carried out. Findings: The results of the three-wave multi-level analysis indicate support for the hypotheses and suggest that future time perspective affects group performance through student engagement. Moreover, group cohesion interacts with student engagement to predict group task performance. Research limitations/implications: The findings show how the application of engagement theory can help in understanding the relationship between two distant variables, namely, future time perspective and group performance. Practical implications: The educators are encouraged to engage students for facilitating the positive impact of future time perspective on group task performance. The findings also imply that the students with future orientation perform well and thus, the educators may need to teach students to have futuristic perspective. Originality/value: This study in one of its kinds to test the mediating role of student engagement between future time perspective and group task performance as well as the interaction effect of group cohesion task with student engagement on group performance at both the individual and group level over a period of time.